2022
DOI: 10.1093/cid/ciac235
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Follow-up Coronavirus Disease 2019 (COVID-19) Antigen Tests After Acute Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection Among Healthcare Personnel

Abstract: We report the utility of rapid antigen tests (RAgT) in a cohort of US healthcare personnel with COVID-19 infection who met symptom criteria to return to work at day 5 or later of isolation. 11.9% of initial RAgT were negative. RAgT can be helpful to guide return to work decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
8
5
0
Order By: Relevance
“…We found that a high percentage of HCWs remained positive on their day 5 and 6 RTW antigen test, consistent with findings by other groups 6,[9][10][11] . With growing data suggesting that a positive COVID-19 antigen test correlates closely with shedding of culturable SARS-CoV-2 virus and likely with contagiousness, these findings merit a re-assessment of the guidance on the optimal time to return HCWs back to work after COVID-19 infection, especially if a RTW antigen strategy is not employed [12][13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that a high percentage of HCWs remained positive on their day 5 and 6 RTW antigen test, consistent with findings by other groups 6,[9][10][11] . With growing data suggesting that a positive COVID-19 antigen test correlates closely with shedding of culturable SARS-CoV-2 virus and likely with contagiousness, these findings merit a re-assessment of the guidance on the optimal time to return HCWs back to work after COVID-19 infection, especially if a RTW antigen strategy is not employed [12][13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
“…An unexpected finding from our study was that vaccinated and boosted HCWs had significantly higher odds of testing positive on their RTW antigen test— independent of the timing of the RTW test and accounting for other demographic variables— when compared to their unvaccinated colleagues (Table 2). This unusual signal was also identified by Tande et al who reported that HCWs who were up to date on their COVID-19 vaccinations were more likely to be positive on their first RTW antigen test compared to those who were unvaccinated or not up-to-date on their vaccines 18 . The study by Landon and colleagues further noted that boosted HCWs were more likely to have a positive RTW antigen test than their non-boosted peers 5 .…”
Section: Discussionsupporting
confidence: 60%
“…RAgT may be useful in guiding isolation decisions and contact tracing, shortening isolation times, and reducing waste of medical resources. Consistent with our results, a recent study reported that RAgT reduced isolation times by 2 days compared with the standard isolation time of 10 days for health care personnel ( 14 ). RAgT would be an important supplement to RT-PCR in SARS-CoV-2 diagnostics and COVID-19 prevention and control.…”
Section: Discussionsupporting
confidence: 92%
“…[11] In a larger sample of 1661 HCWs, 88.1% were antigen positive on Day 5 and antigen positivity was associated with symptomatic infections and vaccinations being up to date. [12] Our findings on antigen-positivity falls between these two prior reports and show that a majority of HCWs might continue to be infectious at 5 days.…”
Section: Discussionsupporting
confidence: 73%
“…Similar to Tande et al, we found that being fully vaccinated and boosted was associated with antigen positivity compared to being unvaccinated. [12] While data demonstrate that boosted individuals were less likely to be infected with Omicron,[13] emerging data suggest those with breakthrough infections might have delayed viral decay and a longer time to viral clearance, which might explain our findings. [14, 15] However, we did not perform viral culture or repeat PCR testing as part of this study.…”
Section: Discussionmentioning
confidence: 93%